USE OF FRUIT CHLOROFORM PARTISI PARE THE WHITE RAT HYPERGLYCEMIC - Pakpahan, Yoana Pratiwi Clara; Suartha, I Nyoman; Anthara, Made Suma; Sudimartini, Luh Made; Dharmayudha, Anak Agung Gde Oka (Buletin Veteriner Udayana; Vol. 9 No. 1 Pebruari 2017, 2017)
This study aimed to determine the efficacy of administration chloroform extract of bitter melon fruit partition to decrease blood glucose levels of hyperglycemic rat ( Rattus norvegicus ). Measurement of blood glucose levels was done before and streptozotocin injected on days -1, 0, 4, 11, and 18 after mice hyperglycemia. Treatment of bitter melon extract and chloroform partition performed after mice hyperglycemia until day 18th. This study consisted of four treatments and five repetitions using a completely randomized design. Four of this treatment is the control of rats (P0), streptozotocin-treated rat with a dose of 40 mg kg (P1), streptozotocin-treated rat with a dose of 40 mg/kg and bitter melon extract 2% (200 mg/kg) (P2) and streptozotocin-treated rat at a dose of 40mg/kg and chloroform partition 50 mg/kg (P3). The results showed that administration of chloroform partition and bitter melon fruit extract significantly ( P <0.05) to decrease the body's blood glucose levels.
Keywords: Hiperglikemia, Momordica charantia, Rattus norvegicus